Antimicrobial applications in agriculture: a review - Ahmad Nor, Yusilawati; Johari, Farahanim; Kamal Ariffin, Fathin Nadhirah; Mohd Ali, Ainoor Mariana; Khairudin, Nurul Hazah (Journal of Pure and Applied Microbiology, 2018)
Antimicrobials receive a great response in agriculture industries. Rapid growth of agriculture products has encouraged huge development of antimicrobial agent to improve growth and health of animals and plants. This paper focuses on the applications of antimicrobial agents such as antibiotics which have been widely used in plants and crops, poultry, aquamarine, and livestock production to inhibit microbial infection by various types of pathogenic microorganisms such as bacteria, viruses, fungi, and parasites. Research related to disease treatment and prevention in agriculture product through proper use of antimicrobial agents is very crucial due to the emergence of bacterial resistance towards antimicrobial drugs. Global concern on the spread of bacterial resistance has gained interest on the research for high potential of antimicrobial agent such as essential oil as it is claimed to have strong antimicrobial activity and safe for humans, animals and plants.